Estimating the public health importance of the CYD-tetravalent dengue vaccine: vaccine preventable disease incidence and numbers needed to vaccinate - Gessner, Bradford D.; Wilder-Smith, Annelies (Vaccine, 2016)
BACKGROUND: To evaluate the potential public health impact of the live attenuated tetravalent Sanofi Pasteur dengue vaccine (CYD-TDV) we analyzed data from the reported clinical trials to calculate vaccine preventable disease incidence (VPDI) and number needed to vaccinate (NNV) based on the licensure indication for persons age 9 years and above. - METHODS: VPDI is defined as incidence in an unvaccinated population X vaccine efficacy (VE), and thus incorporates both VE and the underlying burden of disease. NNV was calculated as 100,000 divided by VPDI divided by 2-year length of study. We compared these values to data for three newer vaccines that are currently integrated into some national immunization programs in Asia and Latin America, namely pneumococcal conjugate, Haemophilus influenzae type b, and rotavirus vaccines. - RESULTS: In the Asian-Pacific trial, in the first 25 months after the first dose of the dengue vaccine, CYD-TDV prevented annually 2639 cases of virologically confirmed dengue for every 100,000 persons vaccinated, for an NNV of 18. In the Latin American trial, given the overall lower annual dengue incidence compared to Asia, VPDI was 1707, and NNV 28. For the Asian-Pacific and Latin American studies, the VPDIs for hospitalized virologically confirmed disease at the trials' end were 638 and 239 per 100,000 population per year, respectively, with NNVs of 75 and 201. VPDI for confirmed dengue hospitalization was higher than that for Hib vaccine against Hib meningitis or all cause severe pneumonia while lower than that for rotavirus vaccine against severe rotavirus gastroenteritis. - CONCLUSIONS: Our analysis found that the CYD-TDV dengue vaccine had favorable VPDI and NNV, also when compared to existing vaccines used in Latin America and Asia. VPDI and NNV varied by serotype distribution, extent of prior dengue exposure (baseline seroprevalence) and country. These findings will help policy-makers decide where and how to introduce this vaccine post-licensure.